USE OF THREE METHODS TO ASSESS THE AMAZONIAN MANATEE (Trichechus inunguis) IN THE TAMSHIYACU TAHUAYO REGIONAL CONSERVATION AREA, LORETO, PERU - OSHITA, Ayumi (2022)
The Amazon manatee (Trichechus inunguis) is endemic to the Amazon Basin, with limited information on population dynamics and currently listed as Vulnerable by the Red List of the International Union for the Conservation of Nature (IUCN). The aim of this study was to compare three methodologies: visual detection (VD), side scan sonar technology (SBL), and surveys to local communities; to detect the presence of the Amazonian manatee and assess the use of these methods for future studies along the species distribution range. The study was carried out within the Tamshiyacu Tahuayo Communal Regional Conservation Areain Iquitos, Peru. The VD resulted in zero sightings at both seasons after a sampling effort of 30 and 29 hours during the rainy and dry seasons respectively. After using the SBL, two individuals were recorded in August, after a total sampling of 103.38 km in the dry season (0.02 ind/km). Surveys to artisanal fishermen in three neighboring communities indicated the presence of manatees and the perception of reduction in sightings within the protected area during 2018 (previous year of this study). We discussed the advantages and disadvantages of each methodology, the logistics associated with its use in complex habitats, and its effectiveness and potential use to detect manatees in future studies in the area.